Psychological sequelae of colonic resections. (17th February 2020) - Powell‐Chandler, A.; Boyce, K.; James, O.; Scourfield, L.; Torkington, J.; Bisson, J.; Cornish, J. A.; ,
Abstract: Aim: The prevalence of anxiety, depression and post‐traumatic stress disorder (PTSD) in the general population has been estimated to be 5.9%, 3.3% and 4.4% respectively. The aim of this study was to determine whether psychological problems are more prevalent following colorectal surgery. Method: Patients who had undergone colorectal resection in a 2‐year period across four centres were asked to complete validated screening questionnaires for anxiety, depression and PTSD (GAD‐7, PHQ‐9, PCL‐5) 12–48 months after surgery. Risk factors were identified using multiple linear regression analysis. Results: After excluding those who had died or received palliative diagnoses, questionnaires were sent to 1150 patients. 371 responded (32.3% response rate); median age 67 (20–99) years; 51% were men. 58% of patients underwent surgery for cancer; 23% had emergency surgery. 28% of patients screened positive for at least one psychological condition, with 20% screening positive for anxiety, 22% for depression and 14% for PTSD. Patients who were younger, women, had surgery as an emergency, for benign conditions, had stomas and had critical care stay were more likely to have poorer psychological outcomes. Multiple linear regression found that only younger age ( P  = 0.000) and female gender ( P  = 0.048) were significant risk factors. Conclusion: The prevalence of anxiety, depression and PTSD appears to be high in patients who have undergone colorectal surgery. Younger patients and women are particularly at risk. Further work is needed to determine how best to prevent, detect and treat people with adverse psychological outcomes following colorectal surgery.